Utilization of recycled concrete fines and powders to produce alkali-activated slag concrete blocks. (10th September 2020) - Ren, Pengfei; Li, Bo; Yu, Jin-Guang; Ling, Tung-Chai
Abstract: This paper investigated the properties of alkali-activated slag (AAS) concrete blocks incorporated with recycled concrete fines (RCFs) and recycled concrete powders (RCPs). They were used as the fine aggregates and the binder in AAS concrete blocks, respectively. The influence of RCFs and RCPs content on water absorption, apparent porosity and compressive strength of AAS concrete blocks was examined. The reactivity of RCPs, mineral changes and microstructure of AAS concrete blocks were characterized by the isothermal calorimetry and X-ray diffraction and scanning election microscope, respectively. The test results indicate that incorporating RCFs and RCPs can decrease water absorption and apparent density of AAS concrete blocks, but an excessive amount of RCFs and RCPs has an opposite impact on these properties. Compressive strength of AAS concrete blocks is enhanced by about 47% when 75% sand is replaced by RCFs. This is mainly attributed to the reaction of un-hydrated cement in RCFs and the internal curing through the RCFs. RCPs have been proven to have a certain degree of reactivity in the alkaline activation. As a result, replacing 20% slag by RCPs can also improve the compressive strength of AAS concrete blocks by about 13%. The AAS concrete blocks produced with RCFs and RCPs possess a satisfactory physical and mechanical properties required for non-load bearing concrete blocks. It is feasible to utilize RCFs and RCPs as the partial replacements of the sand and the binder in AAS concrete blocks, respectively. Graphical abstract: Image 1 Highlights: Recycled concrete fines (RCFs) show better filling effect than sand in AAS blocks. Recycled concrete powders (RCPs) have limited activity in alkali-activated binder. Incorporating RCFs and RCPs decreases water absorption and density of AAS blocks. Replacing sand by RCFs up to 75% improves compressive strength of AAS blocks. Replacing slag by RCPs up to 20% slightly enhances compressive strength of blocks.